Influence of various implant platform configurations on peri-implant tissue dimensions: an experimental study in dog - Baffone, Gabriele M. [UNESP]; Botticelli, Daniele [UNESP]; Pantani, Fabio [UNESP]; Cardoso, Leandro Carvalho; Schweikert, Michael T.; Lang, Niklaus P. (Wiley-Blackwell, 2011)
AimTo evaluate the influence (i) of various implant platform configurations and (ii) of implant surface characteristics on peri-implant tissue dimensions in a dog model.Material and methodsMandibular premolars and first molars were extracted bilaterally in six Labrador dogs. After 3 months of healing, two implants, one with a turned and a second with a moderately rough surface, were installed on each side of the mandible in the premolar region. on the right side of the mandible, implants with a tapered and enlarged platform were used, while standard cylindrical implants were installed in the left side of the mandible. Abutments with the diameter of the cylindrical implants were used resulting in a mismatch of 0.25 mm at the tapered implant sites. The flaps were sutured to allow a non-submerged healing. After 4 months, the animals were sacrificed and ground sections were obtained for histometric assessment.ResultsAll implants were completely osseointegrated. A minimal buccal bone resorption was observed for both implant configurations and surface topographies. Considering the animals as the statistical unit, no significant differences were found at the buccal aspect in relation to bone levels and soft tissue dimensions. The surface topographies did not influence the outcomes either.ConclusionsThe present study failed to show differences in peri-implant tissue dimensions when a mismatch of 0.25 mm from a tapered platform to an abutment was applied. The surface topographies influence a neither marginal bone resorption or peri-implant soft tissue dimension.To cite this article:Baffone GM, Botticelli D, Pantani F, Cardoso LC, Schweikert MT, Lang NP. Influence of various implant platform configurations on peri-implant tissue dimensions: an experimental study in dog.Clin. Oral Impl. Res. 22, 2011; 438-444.
Keywords: animal study; bone healing; bone levels; histometry; oral implants; platform design; soft tissue dimensions